Effect of defoliation and storage of scion stick on growth of softwood graft of mango (Mangifera indica) (Current Horticulture, 2024)
Mango (Mangifera indica L.) is vegetatively propagated by inarching, veneer grafting, epicotyl grafting, softwood grafting, etc. In softwood grafting, it is easy to handle and quite efficient as well as grafts can normally raised within a year, thus reducing cost of raising grafts considerably. The vegetative propagation technique through softwood grafting is much influenced by climatic condition of the region and is mostly carried out on the onset of monsoon, thereby restricting the availability of planting material for a particular season (Uchoi et al., 2012). Therefore, an experiment was conducted to test possibility of propagation of mango by softwood grafting.